(untitled) (Italian Journal of Public Health, 2010)
Background: An educational intervention on Sexually Transmitted Diseases (STDs) accompanied by a multimedia exhibition was proposed in order to verify the effectiveness of an exhibition as a tool for prevention, to increase awareness in youth and to evaluate whether it yielded changes in the sexual behaviour of its’ visitors. The Target population were high schools and university students. Methods: The Exhibition consisted of a historical overview and four other sections: biological and clinical aspects, epidemiology, prevention and a section called the Red Zone with clear and explicit images relating to STDs. The exhibition was supported by three observational studies carried out on about2000 students of two High Schools and the university in the city of Cassino, Italy. Data collection took place through three different types of “ad hoc” questionnaires. The Statistical analysis carried out was that typical of cross-sectional surveys. We utilized the statistical program Epi-Info 3.5. Results: Regarding survey 1, 48% of 529 students taking part said that the exhibition had contributed “enough” for them to acquire new knowledge, 75.2% had already had sexual intercourse and 37.7% of them did not change their sexual habits. Relative to survey 2, 583 responded to the pre test and 403 post- tests returned. Regarding knowledge, data obtained from processing of pre-tests showed how 63.9% of the sample did not know how many STDs existed, whilst this value dropped in post test answers to 49.2% . AIDS was the best known disease (96%) whilst other STDs were little known. The educational intervention partly increased these percentages. With regard to sexual practices although 43% of the sample claimed to have already had sexual intercourse (66% male and 34% female). The family doctor is seen by a high percentage of young people (70% - 68.6%) as the first figure which should address an individual affected by a sexually contracted disease. Only 46% (pre and post tests) recognized at risk groups such as “drug addicts”, homosexuals and heterosexuals. Eight hundred university students participated in Survey 3. The sample had good knowledge about HIV transmission and the AIDS disease and 93% of respondents knew how to avoid infection. They identified drug users and homosexuals as the most prone to infection to HIV, while awareness of infection risk among heterosexuals was less marked. Despite its importance, awareness of condom use was worrying as only 44.2% reported to always one. Conclusions: The exhibition can be considered as an effective prevention tool for new knowledge acquisition but not for the modification of behaviours already present. Even in this study, it looks like the long-term effects, in populations who have had health education interventions with the models of behavioural change, are not sufficiently protective . Therefore, it is necessary to intensify efforts to broadly apply the most effective models of self empowerment in order to change risk behaviours.